Navigating Faith and Finance: The Role of Islamic Literacy and Scepticism in Shaping Cryptocurrency Investment Intention - Fuad Hasyim; Ririn Tri Ratnasari; Sri Herianingrum; Arroyan Ramly; Wakhid Musthofa (Shirkah: Journal of Economics and Business, 2025)
Despite the rapid global adoption of cryptocurrencies, the lack of a unified Sharia ruling creates profound ethical uncertainty for faith-conscious investors. The present study analyses how investors integrate spiritual considerations and the complexities of Islamic Finance to formulate investment intentions in cryptocurrencies. Building on the Decomposed Theory of Planned Behaviour (DTPB), the model incorporates Islamic Financial Literacy and Sharia Scepticism. Shariah Scepticism and Islamic Financial Literacy reflect the Islamic value-embedded attitude towards finance and investment. For this study, the authors collected and analysed survey data from Java’s urban areas' 213 Muslims using PLS-SEM. Results demonstrate that people’s investment intentions are shaped by the compatibility of values, ease of use, and perceived usefulness of the investment. Financial Literacy in Islam bolsters confidence in Shariah-compliant digital assets, and Shariah Scepticism raises theological and ethical considerations. Despite the limited impact of perceived behavioural control, subjective norms exerted the most significant influence on behavioural intentions. This study adds to the Islamic behavioural finance literature the first faith-based model to explain investment intentions in cryptocurrencies within Muslim populations.